STRUCTURAL AND FUNCTIONAL CHARACTERIZATION OF THE LEAF LITTER INSECT FAUNA IN DIFFERENT PLANTS COVERS - SERRA DO ITAJAÍ NATIONAL PARK - Arenhardt, Taise Cristina Plattau; Klunk, Guilherme Alan; Vitorino, Marcelo Diniz (Floresta, 2022)
Insects stand out for their diversity, representativeness, ecological importance, and sensitivity to environmental changes that are affected by anthropogenic changes in natural ecosystems. This study aimed to characterize the leaf litter insect fauna in four different areas that included two native forests and two pastures in Serra do Itajaí National Park. Data were collected from August 2014 to August 2015 from pitfall trap installations. The abundance, richness, diversity, family composition, and functional groups were analyzed. In total, 16,062 individuals were collected that were distributed across 16 orders and 101 families. Abundance, family richness, and diversity were similar among the areas. However, the composition differed, demonstrating that the environments possessed different insect fauna communities based on the composition of families. The Coleoptera order with the Ptiliidae family was more abundant in the native forest, while the Hemiptera (Cercopidae and Cicadellidae) were more abundant in the pasture area. The composition of fungivores and phytophagous fungi differed significantly among the areas. The number of exclusive families and their composition demonstrated a leaf litter insect fauna that was adapted to the environmental conditions and resources available within each environment